Effect of low level laser therapy and bioactive glass in the treatment of periodontal infrabony defects: A randomized controlled clinical trial - Danish, Pathan; Othman, Badr; Altassan, Mousa; Alghaleb, Thamer; Niazi, Adham; Dakhil, Siraj; Aboalela, Ali; Alharbi, Mohammed; Mawardi, Hani (Journal of King Abdulaziz University: Science, 2024)
Background: Several guided bone regeneration techniques have been used in the past aiming to treat infrabony defects with promising outcome. Recently, low level laser therapy (LLLT) has been introduced as an adjunctive tool with better bone and soft tissue healing due to its biostimulation and biomodulation properties. The aim of the present study is to evaluate the adjunctive effect of Gallium – Aluminium – Arsenide (GaAlAs) laser in the management of periodontal infrabony defects. Materials and method: This was a randomised controlled, double blinded, split mouth clinical study carried out on subjects with bilateral infrabony defects. Clinical parameters of plaque index (PI), gingival index (GI), probing pocket depth (PD) and clinical attachment level (CAL) were recorded as well as infrabony defect depth using radiovisiograph at baseline, 3 months and 6 months intervals. The test group was treated with bioactive glass and GaAlAs laser on the 1st, 3rd, 5th and 7th day following periodontal open flap surgery and the control group received bioactive glass only. All data were collected and analyzed using Wilcoxon signed rank test and paired t test. Results: A total of 15 subjects were enrolled in this study. There was a significant reduction in the PD (p=0.05), CAL (p=0.01) and in defect depth observed at 6 months interval in the test group compared to control group. Conclusion: Based on the current data, the application of LLLT as an adjunctive tool with bioactive glass may have a superior outcome in treating infrabony defects compared to bioactive glass alone.